2013
DOI: 10.1590/s0100-83582013000300011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ecological factors on germination of horse purslane (Trianthema portulacastrum)

Abstract: -Trianthema portulacastrum is a very problematic summer crop weed and a complete crop failure has been observed because of this weed at high density. The effect of different ecological factors on germination of T. portulacastrum seeds collected in two different years (2009 and 2005) was studied in laboratory experiments. An increase in temperature from 25 to 35 o C increased germination percentage of T. portulacastrum from 65 to 85%, after which germination started to decrease, reducing to 71.25% at 45 o C. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…tenuifolius (rapid reduction after -0.2 MPa, 50% by -0.38 MPa) [ 13 ]. By contrast, Trianthema portulacastrum (horse purslane) was less affected by moisture stress, with a 50% reduction in maximum germination at -0.50 MPa [ 6 ]. This indicates that in a situation of competition between these weeds, Trianthema portulacastrum would be the least affected by lack of moisture than all the other species, but S .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…tenuifolius (rapid reduction after -0.2 MPa, 50% by -0.38 MPa) [ 13 ]. By contrast, Trianthema portulacastrum (horse purslane) was less affected by moisture stress, with a 50% reduction in maximum germination at -0.50 MPa [ 6 ]. This indicates that in a situation of competition between these weeds, Trianthema portulacastrum would be the least affected by lack of moisture than all the other species, but S .…”
Section: Resultsmentioning
confidence: 99%
“…Environmental factors, such as temperature, light, pH, osmotic and salt stress affect the germination or emergence of weeds [ 6 ], [ 7 ], [ 8 ], [ 9 ]. Some weeds have a narrow tolerance range, while others are able to germinate over a wide range of temperatures [ 10 ], [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, B. excelsa seeds present physiological dormancy, which results in slow, irregular, and low percentages of germination (Kainer et al, 1999a;Auca et al, 2018). Seed burial depth and food reserves within seeds are the most important factors affecting seed germination (Tanveer et al, 2013;Baskin & Baskin, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Tanveer et al . () reported that high infestation of Trianthema spp. may result in complete crop failure.…”
Section: Introductionmentioning
confidence: 99%